Immature stages of Asteriza flavicornis (Olivier) and Physonota alutacea Boheman (Coleoptera: Chrysomelidae: Cassidinae) - Świętojańska, Jolanta; Windsor, Donald M. (Fundacja Natura optima dux, 2008)
The first instar larva of Physonota alutacea Boheman, 1854, a member of thetribe Physonotini Spaeth, 1942, and the mature larva and pupa of Asteriza flavicornis(Olivier, 1790), a member of the tribe Asterizini Hincks, 1952, are described for the firsttime. The mature larva and the pupa of Physonota alutacea are redescribed. Immaturesare figured and described using light microscopy, the first instar larva of Physonotaalutacea using scanning electron microscopy. Similarities in the larval morphologies of Cistudinella Champion, 1894, a member of the tribe Ischyrosonychini, Chapuis, 1875, and Physonota suggest both genera are close phylogenetically and should be placed in a single tribe. The additional similarities between the mature larva of Asteriza and those of Physonota and Cistudinella suggest all three genera should be placed within a single tribe.
Bibliogr. s. 665
S. 641-665 : il. ; 27 cm
Nazwy taksonów w jęz. łac.
Keywords: Coleoptera; Chrysomelidae (Coleoptera); Cassidinae; Physonotini; Asterizini; Physonota alutacea; Asteriza flavicornis; morphology of immatures; Neotropics